1996
DOI: 10.1210/endo.137.5.8612532
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic protein-1-mediated insulin-like growth factor gene expression in primary cultures of rat osteoblastic cells.

Abstract: Osteogenic protein-1 (OP-1) is a member of the bone morphogenetic protein family and has been shown to induce new bone formation in vivo. In the present study, we determined whether the expression of the IGF system, a significant growth factor system in bone, was altered by OP-1 in primary cultures of fetal rat calvarial cells. Levels of messenger RNA (mRNA) encoding insulin-like growth factor I (IGF-I), IGF-II, IGF-I receptor, and IGF-binding proteins (IGFBP-1 to -6) were determined after OP-1 treatment. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
28
1
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 15 publications
5
28
1
1
Order By: Relevance
“…Compared with the control group without growth factor, addition of OP-1 stimulated an additional 10% increase in bone formation, which agrees with our previous experiment, in which OP-1 was pipetted at 330 ng/ml daily (data not shown), and studies from other laboratories demonstrating OP-1 stimulates the differentiation of osteoprogenitor cells [2,28,29,[31][32][33]. Differentiation of the osteoprogenitor cells without addition of growth factors was synchronous with an increase of OC between Days 15 and 20 followed by a slower increase later on (slope of 0.44) (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Compared with the control group without growth factor, addition of OP-1 stimulated an additional 10% increase in bone formation, which agrees with our previous experiment, in which OP-1 was pipetted at 330 ng/ml daily (data not shown), and studies from other laboratories demonstrating OP-1 stimulates the differentiation of osteoprogenitor cells [2,28,29,[31][32][33]. Differentiation of the osteoprogenitor cells without addition of growth factors was synchronous with an increase of OC between Days 15 and 20 followed by a slower increase later on (slope of 0.44) (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Further analysis is needed to determine the mechanisms by which BMP-7 and Dex regulate IGFBP-5 and FHL-2 in bone. In contrast to our observed increase in IGFBP-5 expression in human osteosarcoma cells following BMP-7 treatment, previous data have been reported that IGFBP-5 mRNA expression decreased in primary rat calvaria cells following BMP-7 treatment [38][39][40]. These data suggest that IGFBP-5 response to BMP-7 treatment may be species and/or celltype specific.…”
Section: Coordinated Expression Of Igfbp-5 Fhl-2 and Adam-9 In Respcontrasting
confidence: 99%
“…Smads up-or down-regulate the transcription of a subset of target genes that includes Runx2 (12). BMP-7, also known as the osteogenic protein-1 (OP-1), has been found to induce new cartilage and bone formation in vitro and in vivo (13-15) and regulate cell proliferation and differentiation (16,17). OP-1 blocks cartilage damage caused by Fn-f and may promote repair by enhancing proteoglycan and collagen synthesis (18).…”
mentioning
confidence: 99%
“…2 Yeh and colleagues (17,23) have presented data indicating that IGF-1 gene expression may be up-regulated by OP-1 at both transcriptional and post-transcriptional level in osteoblastic cells. IGF-1 is a polypeptide that exerts anabolic/anticatabolic effects on cartilage.…”
mentioning
confidence: 99%